Performance of strawberry plants against different spectra of complementary artificial radiation in cultivation without soil - Machado, José Tobias Tobias Marks; Tonin, Jeferson; Sobucki, Lisiane; Rohrig, Bruna; Vignolo, Gerson; Betemps, Débora Leitzke; Schneider, Evandro Pedro (Revista de Ciências Agroveterinárias, 2018)
Among the various inputs used in strawberry cultivation, complementary artificial radiation has been a tool used in crops of high added-value. The this study was to evaluate the agronomic effects of complementation with photosynthetically active radiation in different spectra on strawberry crops, using fluorescent lamps in protected cultivation without soil. A completely randomized design with four replicates was used. The treatments encompassed the emission of radiation in different spectral ranges, using white, blue and red fluorescent lamps, and the combination of blue and red lamps. There was a control group without complementary radiation. Physiological, phenological and production aspects were evaluated. The use of combined blue and red lamps, and of white lamps, anticipated flowering and increased the mass of fruit produced over the crop cycle. Blue lamps induced the production of fruits with great mean mass. Red lamps had no effects on the increase in production nor on the anticipation of flowering.